The tax system and the financial crisis - Ceriani, Vieri; Manestra, Stefano; Ricotti, Giacomo; Sanelli, Alessandra; Zangari, Ernesto (PSL Quarterly Review, 2011)
This paper investigates the effects of the tax system on the economic factors that triggered the financial crisis. We examine three cases in which the tax regime interacted with these factors, reinforcing them. First, we focus on the taxation of residential building: while the importance of capital gains taxes is disputed, the deductibility of mortgage interest may have contributed to the financial crisis by creating some of the raw materials for the securitization industry. Second, a narrow perspective on the tax treatment, together with specific provisions, may have fostered performance-based remuneration of managers, resulting in overemphasis of short-term profitability and incentive to excessive risk-taking. Third, the securitization process, which played a key role in the outbreak of the financial crisis, was accompanied by opportunities for tax arbitrage and reduction of the overall tax wedge paid by investors, through offset of incomes that are ordinarily taxed at different rates; a de facto exemption of CDS premiums received by non-residents supplemented the tax arbitrage. JEL Codes: H31, H32, G01, R21